Weed Management in Clover -- 2005 - Jason A. Ferrell (EDIS)
Cool-season clovers are important for grazing systems in Florida. Clover provides grazing flexibility during winter and spring while warm-season grasses/forages are dormant. Weeds are problematic in clover fields and weed control can be more challenging because clover plants are sensitive to many pasture herbicides. There are also fewer herbicide products registered for use on clover compared to other forage species, so chemical weed control programs have to be chosen carefully. Table 1 provides information on herbicides that can be applied for weed control in clover production systems. This document is SS-AGR-235, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published January 2005.